Computational methods for eikonal differential cross sections. - Miraglia, J. E.; Piacentini, R. D.; Rivarola, R. D. (North Holland Publishing Co., 1980)
Fil: Miraglia, J. E. Comisión Nacional de Energía Atómica; Argentina